Оценка эффективности инновационных проектов на ранних стадиях проектирования - Сударкина, Светлана Петровна (НТУ "ХПІ", 2017)
В статье рассматриваются проблемы адекватной оценки эффективности инновационных проектов в условиях ограниченности исходных данных, характерных для ранних стадий проектирования и разработки проекта – возможный уровень затрат, предполагаемая техническая результативность, экономическая эффективность проекта, риски.

In the article the problems of adequate estimation of innovative projects efficiency are examined in the conditions of limit nature of basic data characteristics for the early stages of design, planning and development of project – it is a possible level of expenses, supposed technical effectiveness, economic and social efficiency of project, risks, etc.. A difference is shown between the methods of calculation and parameters of efficiency for the projects with different level on the inlaid facilities, terms of realization, the level of risks, etc. The question of choice of project variants realization is considered depends on correlations between the level of investments and getting net income, which is formed the size of net present value. Influence of change of investments is appraised on eventual economic efficiency of рroject. It is suggested to use the index of relative change of term of return of expenses and to compare its size with the possible rejection point of investment return from a moment completion, according with the planned calculation.
Estimation of efficiency of innovative projects on the yearly stages of design
Keywords: инновационные проекты; инвестиции; ранние стадии проектирования; экономические параметры; прибыль; критерии эффективности проектов; риски; innovative projects; early stages of planning; technical effectiveness; level of expenses; economic efficiency; methods of calculation; parameters of efficiency; risks; term of return of expenses